As transformações da imagem fotográfica - Leite, Miriam Lifchitz Moreira (Revista de Antropologia, 1998)
In his last years, Brassaï examined life, thought and narrative technique in Marcel Proust Works as na gigantesque photo, with revealing changes of perspective, angles? and frames of reference. In front of na eclectic bibliography about Death and Dying, where the authors are constantly searching for the adequade way to express not being, I choose the grandmother death, in A busca do tempo perdido as unique in his way to express himself by photographic metaphors and alusions.